2004
DOI: 10.1097/00004836-200403000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin in the Short- and Long-term Control of Dyspepsia Symptoms in Patients with Gastroparesis

Abstract: Treatment of gastroparesis with low-dose erythromycin and low-bulk diet results in a dramatic short-term improvement in the majority of patients. Short-term response predicts long-term response. This response may not be as great, possibly due to tachyphylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 44 publications
1
36
1
Order By: Relevance
“…Since the duration of postoperative abomasal hypomotility is unknown (Wittek et al 2005), erythromycin was applied three times at intervals of 24 h in the Emy3 study group. In human medicine, low doses of this drug are administered repeatedly to increase gastric emptying in patients with gastroparesis and, thus, to facilitate a sustained clinical benefit (Dhir and Richter 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Since the duration of postoperative abomasal hypomotility is unknown (Wittek et al 2005), erythromycin was applied three times at intervals of 24 h in the Emy3 study group. In human medicine, low doses of this drug are administered repeatedly to increase gastric emptying in patients with gastroparesis and, thus, to facilitate a sustained clinical benefit (Dhir and Richter 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review, Camilleri 47 concluded that erythromycin is most useful in acute gastroparesis and recommended a regimen that begins with intravenous erythromycin lactobionate (3 mg/kg every 8 hours) and continues with oral administration (250 mg three times a day) for 5 to 7 days. 47 Efficacy with long-term oral administration has been less obvious 48,49 and may be complicated by the risks associated with long-term antibiotic use 49 ; in general, data remains scanty. 50 There is also evidence that the salutory response to erythromycin may be blunted by hyperglycemia.…”
Section: Macrolidesmentioning
confidence: 99%
“…The sample size was never more than 13 and the treatment duration was 4 weeks. Two recent studies, again with small sample sizes, have reported conflicting results regarding the effectiveness of ER in the treatment of gastroparesis [18,19].…”
Section: Off-label Administration Of Erythromycinmentioning
confidence: 99%